Impact of Green Marketing Elements on Consumers: A Behavioral Approach - Quynh, Pham Ngoc Huong; Thu, Cuc Ly; Pandey, Krishan K.; Phuong, Nguyen Van (Ital Publication, 2025)
This research examines the factors influencing green purchasing behavior in the Vietnamese market, utilizing the Theory of Planned Behavior (TPB) as its foundation. Utilizing an online questionnaire survey of 596 Vietnamese consumers from December 2023 to February 2024, the research examines the influence of key factors, including green advertising, awareness of green products, environmental awareness, subjective norms, attitude toward green products, and green pricing on consumer purchase intentions and behaviors. The research utilized the technical of Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine and confirm the proposed hypotheses. The findings reveal that the most influential factor on consumer purchase intentions and behaviors is the attitude toward green products, highlighting the crucial role of consumer perceptions and values regarding environmentally friendly products. Furthermore, green advertising and awareness of green products also play a vital role in shaping consumer intentions. While subjective norms and green pricing also show an influence, they have a lesser impact. This study contributes both theoretically and practically by offering valuable insights for marketers and policymakers designing effective green marketing strategies that enhance consumer engagement and encourage the adoption of environmentally friendly products in Vietnam.